Theology and ethics in Adam Smith: A case for Islamic Economics - Naser, Mohammad Wasim (Intellectual Discourse, 2018)
Abstract: This study is an analysis of the theological and ethical dimensions in the writings of Adam Smith. It deals with aspects of philosophy and intellectual history. By revealing the theological and ethical roots of Smith’s writings in the formation of modern economics, arguments for an economics that is based on Islamic foundations become stronger. The study will therefore lay out the basic moral project of Smith and then contextualize it in the Western Enlightenment tradition. It shows how religious discourses were instrumental in shaping the thoughts and ideas of Enlightenment in general, and economics in particular. The study will then give a brief overview of traditional Islamic theology and ethics in order to give directions for future research.